The Effect of Job Stress on the Performance of Production Department Employees at PT Saurindotex Mandiri - Ramdan, Rizki Hari; Kristanto, Yudi; Darka, Darka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The decline in employee performance at PT Saurindotex Mandiri can be caused by several factors. Factors that influence performance include work stress and the work environment. The phenomena that occur include decreased employee performance, high levels of employee stress and an unsupportive work environment. The objectives of this research are 1. To find out work stress at PT Saurindotex Mandiri, 2. To find out employee performance at PT Saurindotex Mandiri, 3. To find out whether or not there is an influence of work stress on employee performance at PT Saurindotex Mandiri, this research, which used quantitative methods with associative techniques, was carried out at PT Saurindotex Mandiri with a population of 86 employees with data collection techniques using questionnaires. Based on the results of the research conducted, the results of testing the multiple linear regression equation Ý = 7.822 + (-0.187) X1 can be used to explain the form of a linear relationship between work stress and employee performance. Simple linear regression equation Ý = 7.822 + (-0.187) constant 7.822.